DAYA TARIK WISATA PADA MUSEUM KEPRESIDENAN BALAI KIRTI, BOGOR 130 TOURIST ATTRACTION OF PRESIDENTIAL MUSEUM BALAI KIRTI, BOGOR - Hamidah, Siti (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2019)
This article discusses about Presidential Museum’s tourist attraction that could be developed as the part of historical tourism in Bogor. Author uses Qualitative Research Methods and descriptive analysist-data. Result shows that Presidential Museum’s tourist attraction lies on the building, collections and activities/events held in museum.